The impact of Fed rate cut on CNY exchange rate: Empirical analysis based on vector autoregressive model - Wang Xulin (SHS Web of Conferences)
This paper focuses on the influence mechanism of Fed rate cut on China’s exports (EX) and CPI and uses an extended vector auto regressive model (VAR) to analyze its linkage effect with the CNY exchange rate (ER). The core variables are sorted out, global macroeconomic data from 2015 to 2024 are integrated, and a VAR model including CPI, Fed interest rate, EX and M2 is constructed. The empirical findings indicate that the Fed rate cut will push up the CNY exchange rate through the capital flow channel in the medium run, but at the same lower China’s CPI; While the expansion of the money supply has a lagged effect on the transmission of CPI, export growth has a substantial positive support for the exchange rate over the long term. The variance decomposition shows that the Fed policy contributed 35% to the initial exchange rate fluctuations but was gradually replaced by exports (28%) and China M2 growth (22%) over time. Based on this, this paper proposes a dynamic monetary policy coordination framework and emphasizes the importance of export competitiveness and inflation expectation management.